Infrastructure, economic growth and population density in Turkey - Mehmet Aldonat Beyzatlar; Yeşim Kuştepeli (International Journal of Economic Sciences and Applied Research, 2011)
Transportation infrastructure is an exciting topic for public policy, private sector and the connection between them. This study deals with the impact of railways as hard type of transportation infrastructure on economic growth and population density. The purpose of this study is to search for historical relationships between railway infrastructure and economic growth; and between railway infrastructure and population density in Turkey. By using annual data for 1950-2004, both tangible and intangible effects of railway infrastructure are aimed to be estimated. The results form cointegration and causality tests imply that there is a positive long run relationship between railway length and population density and between railway length and real GDP per capita. Railway length causes real GDP per capita to increase only in the long run but it causes population density to increase both in the long and the short run. These results confirm the theoretical framework that improvements in transportation infrastructure lead to higher income and higher population in the investigated area.
Keywords: H54; O40; L92; 330; hard types of infrastructure; public policy; transportation systems; railways; causality